2018
DOI: 10.1155/2018/5092064
|View full text |Cite
|
Sign up to set email alerts
|

Automated Region Extraction from Thermal Images for Peripheral Vascular Disease Monitoring

Abstract: This work develops a method for automatically extracting temperature data from prespecified anatomical regions of interest from thermal images of human hands, feet, and shins for the monitoring of peripheral arterial disease in diabetic patients. Binarisation, morphological operations, and geometric transformations are applied in cascade to automatically extract the required data from 44 predefined regions of interest. The implemented algorithms for region extraction were tested on data from 395 participants. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…This algorithm worked perfectly for all the current images when compared with the ground result. Generally, it will be possible to make an initial decision based on the visual inspection [28] to verify if the segmentation corresponding to an ROI was extracted correctly or not. In this inspection, it was found that the proposed algorithm, perfectly does the background-foreground segmentation.…”
Section: Resultsmentioning
confidence: 99%
“…This algorithm worked perfectly for all the current images when compared with the ground result. Generally, it will be possible to make an initial decision based on the visual inspection [28] to verify if the segmentation corresponding to an ROI was extracted correctly or not. In this inspection, it was found that the proposed algorithm, perfectly does the background-foreground segmentation.…”
Section: Resultsmentioning
confidence: 99%
“…Each plantar foot was divided into 11 regions of interest (ROIs) [55,71] shown in Fig- ure 3b: ROIs 1 to 5 are the toes, ROIs 6 to 8 are the metatarsal areas of the foot and finally ROIs 9 to 11 are the ones situated on the heel of the foot. For each one of these regions, the mean temperature, the standard deviation (SD) and the maximum value were extracted Measurements were made at the affected and contralateral extremities at baseline (right after the injection of the local anesthetic) and 10 min after the injection of the medication.…”
Section: Regions Of Interestmentioning
confidence: 99%
“…Screening is the key to detecting early-stage disease and allows the initiation of optimal preventive medical treatment, which may reduce modifiable risk factors for patients at risk for arteriosclerotic disease [43]. An emerging modality that in the future could have an impact on detection of PAD is medical thermography, which has been shown to detect higher forefoot temperatures associated with this condition in type 2 diabetes mellitus [44,45].…”
Section: Diabetes Foot Screening Guidelines Related To Pamentioning
confidence: 99%